Faktor-Faktor Pengaruh Pemilihan Peminatan Mahasiswa di Program Studi Pendidikan Kesejahteraan Keluarga Fakultas Teknik UNJ - Erika Dosista; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Institut Nalanda, 2023)
Education is a purposeful and systematic endeavor designed to create an atmosphere and learning process facilitating active development of learners' potential, encompassing spiritual dimensions, self-discipline, character, intelligence, ethical values, and skills essential for personal, community, national, and state interests. This study seeks to examine the factors influencing students' choices of majors within the Family Welfare Education Program at the Faculty of Engineering, State University of Jakarta (UNJ). Employing a qualitative approach, in-depth interviews were conducted with students who had already made their major selections. The results highlighted pivotal factors impacting students' decisions, such as personal interests and talents, family influence, guidance from professors and academic advisors, and career expectations. These findings offer profound insights into the decision-making process related to major selection among students. Recommendations for future research involve expanding sample sizes, employing a mixed-methods approach, delving into contextual factors, exploring changes in the academic landscape, and considering technological advancements affecting students' choices. Comparative research across diverse higher education institutions can provide a more comprehensive understanding of student decision-making, ultimately contributing to the development of more effective strategies to assist students in aligning their majors with their interests, talents, and career aspirations.